Level of Services Provided at Sports and Recreational Events in the Kingdom of Saudi Arabia - Al-Salawi, Abdullah bin Ahmed; bin Said, Saad bin Walid (Journal of Physical Education, 2026)
Objective This study aimed to identify the level of services provided in sports and recreational events The descriptive method was used on a sample of (657), who were randomly selected from three major cities in Saudi Arabia. Randomly selected from three major cities in the Kingdom of Saudi Arabia. The questionnaire was the data collection tool, and the results of this study found that the level of services The level of services provided at sports and recreational events in the Kingdom of Saudi Arabia came at an average level, and the services provided by females Their level is higher than males, as well as those who attend with family and relatives, the services provided better than those who attend alone, and there was no difference in the level of services provided in recreational sports events at the level of social status and place of residence, so the researchers recommended that attention be paid to increasing the services provided at recreational sports events Especially technical and logistical services. While improving the ease of obtaining tickets electronically and offering them before a period of time commensurate with the event. Conduct more studies such as: The impact of technical services on the visitor experience at sporting events. And a study Analyzing the gaps between visitors’ expectations and the level of services provided, and evaluating marketing strategies to attract visitors and improve satisfaction, and study the role of social factors in the role of social factors in the visitor experience during events. The study of optimizing the ticketing experience: new mechanisms for online shopping.